VIOLÊNCIAS DO ESTADO E SEGURANÇA PÚBLICA EM MOÇAMBIQUE PÓS-INDEPENDÊNCIA - Albino Massimacu (Universidade Federal do Maranhão, 2019)
This article, intends to discuss the practices of State violence in Mozambique. Since the political independence achieved in 1975 and the subsequent constitution of the Mozambican State, citizens have questioned its role in public security, as well as in the guarantee of human rights, since, at certain times when social tensions become more acute, this same State, through the police, uses violence as a means of silencing them. It starts from the assumption that the different practices of violence and, particularly, the violence of the State have assumed a special role and with it the aggravation of the feeling of public insecurity. For the effectiveness of this work, bibliographic material of specialist authors on violence and works on the situation of public security in Mozambique from political independence to the present were used. Finally, it shows that the Mozambican State has used violence as a way to repress these social tensions.